2011
DOI: 10.1021/ic2021676
|View full text |Cite
|
Sign up to set email alerts
|

Formation of the Imide [Ta(NMe2)3(μ-NSiMe3)]2 through an Unprecedented α-SiMe3 Abstraction by an Amide Ligand

Abstract: Ta(NMe(2))(4)[N(SiMe(3))(2)] (1) undergoes the elimination of Me(3)Si-NMe(2) (2), converting the -N(SiMe(3))(2) ligand to the ═NSiMe(3) ligand, to give the imide "Ta(NMe(2))(3)(═NSiMe(3))" (3) observed as its dimer 4. CyN═C═NCy captures 3 to yield guanidinates Ta(NMe(2))(3-n)(═NSiMe(3))[CyNC(NMe(2))NCy](n) [n = 1 (5), 2 (6)]. The kinetic study of α-SiMe(3) abstraction in 1 gives ΔH(‡) = 21.3(1.0) kcal/mol and ΔS(‡) = -17(2) eu.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…The optimized structure of D, which is shown below eqn (1), reveals an excellent correspondence to the reported X-ray diffraction structure. The computed internuclear Ta⋯Ta distance of 3.191 Å, which is slightly longer (0.028 Å) than that distance found in the solid-state structure, 27 argues against any significant bonding between the two metal centers. 38 The Wiberg index of 0.14 for the Ta-Ta vector in D underscores this assertion.…”
Section: Resultsmentioning
confidence: 53%
See 4 more Smart Citations
“…The optimized structure of D, which is shown below eqn (1), reveals an excellent correspondence to the reported X-ray diffraction structure. The computed internuclear Ta⋯Ta distance of 3.191 Å, which is slightly longer (0.028 Å) than that distance found in the solid-state structure, 27 argues against any significant bonding between the two metal centers. 38 The Wiberg index of 0.14 for the Ta-Ta vector in D underscores this assertion.…”
Section: Resultsmentioning
confidence: 53%
“…Heating Ta(NMe 2 ) 4 [N(SiMe 3 ) 2 ] in the absence of a trapping agent gives the imide-bridged dimer [Ta(NSiMe 3 )(NMe 2 ) 3 ] 2 (D) and Me 3 SiNMe 2 (C); the molecular structure of the former product has been established by X-ray diffraction analysis and presumably results from the dimerization of the intermediate imide complex Ta(NSiMe 3 )(NMe 2 ) 3 (B). 27 DFT analysis of this reaction has confirmed that the α-elimination is a concerted process and is stereospecific, insomuch as only A2 reacts to give the expected products Ta(NSiMe 3 )(NMe 2 ) 3 (B) and Me 3 SiNMe 2 (C). Species A1 and A3 do not allow the reacting amido groups to achieve the requisite orientation for the formation of the critical cyclic transition state associated with the transfer of the Me 3 Si group to the adjacent Me 2 N acceptor ligand.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations